Answer:
i think its a uhh a carrot?? no the answer is 6
Step-by-step explanation:
beetlejuice
Answer:
A
Step-by-step explanation: Your salary will be greater than or equal to $46,000.
Answer:
Kenny is 18 years old Andrew is 10 years old Tim is 30 years old and Cameron is 5 years old
Step-by-step explanation:
Let a be Kenny's age , b be Andrew's age , c be Tim's age , d be Cameron's age
( b < a , b<c , d<b)
Kenny is 8 years older than Andrewn = > a = b + 8 (1)
Tim is 3 times as old as Andrew => c = 3 . b (2)
Cameron is 5 years younger than Andrew => d = b-5 (3)
The combined age of the four is 63 => a+b+c+d = 63 (4)
(1),(2),(3),(4) => b+8 + b + 3b + b-5 = 63 <=> 6b + 3 = 63 <=> b = 10
=> a= 10+8 =18, c = 3 . 10 = 30, d= 5
Complete question :
Suppose the average yearly salary of an individual whose final degree is a master's is $41 thousand less than twice that of an individual whose final degree is a bachelor's. Combined, two people with each of these educational attainments earn $118 thousand. Find the average yearly salary of an individual with each of these final degrees.
Answer:
Bachelors = $53000
Masters = $65000
Step-by-step explanation:
Given that :
Let Salary of bachelor's degree holder = b
Salary of Master's degree holder = 2b - 41000
Master's + bachelor's salary = $118,000
Hence,
2b - 41000 + b = 118,000
3b = 118000 + 41000
3b = 159000
b = 159000 / 3
b = $53,000
Bachelor's degree salary = $53,000
Master's degree salary ; 2b - 41000
2(53000) - 41000 = 65000
A
f(x) = 2x + 1
f(3) = 2*3 + 1 = 7
B
g(x) = x^2
g(7) = 7^2
g(7)= 49
C
f(g(x)) = 2(g(x) + 1
f(g(x)) = 2 x^2 + 1
f(g(3) = 2* 3^2 + 1
f(g(3) = 19
D
g(f(x)) = (f(x))^2
g(f(x)) = (2x + 1)^2
g(f(3)) = (2*3 + 1)^2 = (6 + 1)^2 = 49
E
f(g(x)) = 2*g(x) + 1
f(g(x)) = 2*x^2 + 1
f(g(3)) = 2*3^2 + 1
f(g(3)) = 2 * 9 + 1
f(g(3)) = 18 + 1
f(g(3) = 19
F
f(g(x)) = 2(g(x)) + 1
f(g(x)) = 2*x^2 + 1